WARISAN BUDAYA KARO YANG TERANCAM: UPAYA PELESTARIAN DAN PENGEMBANGAN TRADISI TOPENG TEMBUT-TEMBUT - Cristie Agustina br Angkat; Muhammad Zidan Hakim Lubis; Lestari Dara Cinta Utami Ginting (Jurnal Cakrawala Ilmiah, 2024)
Topeng Tembut-Tembut tradition is one of the customary traditions that developed in the life of Karo people, especially in Tigapanah sub-district and Seberaya Village, Karo Regency. It is a very traditional tradition and has sacred value, believed by the citizens. The procession needed to explain the ups and downs of the Tembut-Tembut mask tradition in Seberaya Village involves local village children. The purpose of this study is to explain and reveal the efforts made by the Seberaya village community in explaining the ebb and flow of the Tembut-Tembut mask tradition in Seberaya Village. The Tembut-Tembut mask tradition is one of the traditional arts that is different from other regional mask arts. The function and meaning of the Tembut-Tembut mask in Seberaya Village are related to the idea of form definition, visual elements, and mask characters. The Tembut-Tembut mask in Seberaya Village is also related to the rainwater summoning ceremony during the dry season. This research uses the historical method in accordance with the collection of sources by directly interviewing informants who are heirs of the Tembut-Tembut mask owner. This paper is expected to be seen and increase the interest of the younger generation to maintain the Tembut-Tembut mask tradition, especially in Seberaya village.